2020
DOI: 10.1111/tpj.14630
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of six Juglans species reveals disease‐associated gene family contractions

Abstract: † These authors are joint first authors. SUMMARYJuglans (walnuts), the most speciose genus in the walnut family (Juglandaceae), represents most of the family's commercially valuable fruit and wood-producing trees. It includes several species used as rootstock for their resistance to various abiotic and biotic stressors. We present the full structural and functional genome annotations of six Juglans species and one outgroup within Juglandaceae (Juglans regia, J. cathayensis, J. hindsii, J. microcarpa, J. nigra,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 82 publications
3
29
0
Order By: Relevance
“…The genome of J. regia contained expanded in 2025 gene families, contracted in 243, and 57 were rapidly evolving gene families (+50/−7; Figure 4c; Table S18). In a comparison of the two walnut genomes, we found that gene families associated with pathogen resistance, including wall-associated receptor kinase (WAK;Trouern-Trend et al, 2020), late embryogenesis abundant protein (LEA; Gao et al, 2020), pathogenesis-related protein (PR; Ozyigit et al, 2017;Soh et al, 2012;Zhao et al, 2015), and PPR repeat (PPR; et al, 2016) were significantly contracted (rapidly evolving; family-wide p-value ≤ .01) in J. mandshurica (Figure 4d; Table S18). The nine plant species genomes we studied in detail were highly divergent in terms of the amount of expansion or contraction in these four gene families; even the closely related species J. regia and J. mandshurica were markedly different in terms of levels of expansion.…”
Section: Unique Paralogues Function and Gene Family Evolution Of J Mandshuricamentioning
confidence: 99%
See 2 more Smart Citations
“…The genome of J. regia contained expanded in 2025 gene families, contracted in 243, and 57 were rapidly evolving gene families (+50/−7; Figure 4c; Table S18). In a comparison of the two walnut genomes, we found that gene families associated with pathogen resistance, including wall-associated receptor kinase (WAK;Trouern-Trend et al, 2020), late embryogenesis abundant protein (LEA; Gao et al, 2020), pathogenesis-related protein (PR; Ozyigit et al, 2017;Soh et al, 2012;Zhao et al, 2015), and PPR repeat (PPR; et al, 2016) were significantly contracted (rapidly evolving; family-wide p-value ≤ .01) in J. mandshurica (Figure 4d; Table S18). The nine plant species genomes we studied in detail were highly divergent in terms of the amount of expansion or contraction in these four gene families; even the closely related species J. regia and J. mandshurica were markedly different in terms of levels of expansion.…”
Section: Unique Paralogues Function and Gene Family Evolution Of J Mandshuricamentioning
confidence: 99%
“…The population genetics, morphology, and diversity of J. mandshurica have been described (Aradhya et al, 2007;Dang et al, 2015;Hu et al, 2017;Liu et al, 2020;Manning, 1978;Zhang et al, 2019), but in general, interest in J. mandshurica based on its potential as a tertiary germplasm pool for improvement of J. regia (Chen et al, 2015;Hu et al, 2016;Ji et al, 2020;Trouern-Trend et al, 2020;Zhou et al, 2017). Wild populations of J. mandshurica and cultivated orchards of Persian walnut (J. regia) grow sympatrically (Dang et al, 2019) but hybridization between these two walnut species is reportedly rare (Shu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pterocarya stenoptera C. DC. is a native deciduous tree of the maple genus in the Juglans family (Trouern-Trend et al 2020). It is primarily found in the forests along streams, river beaches, and wet mountain slopes below 1500 meters above sea level in China and the Korean Peninsula.…”
Section: Introductionmentioning
confidence: 99%
“…It is a diploid plant with 16 chromosomes (2n = 2x = 32) that belongs to the group of species called Asian butternuts (section Cardiocaryon ) that also includes Japanese walnut (J. ailantifolia ) and Manchurian walnut (J. mandshurica ) ( Figure 1; Zhao et al, 2018;Bai et al, 2016;Zhao et al, 2014). Chinese walnut is less valuable as a commodity than its close relative, Juglans regia (Persian or common walnut; Han et al, 2016;Dang et al, 2016;Feng et al, 2018), but Chinese walnut has been evaluated in breeding programs for its resistance to lesion nematodes (Trouern-Trend et al, 2020). In addition, Chinese walnut has potential as a medicinal crop (Yu et al, 2011;Li et al, 2013;Li et al, 2008;Sun et al, 2012;Bi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%